2021
DOI: 10.1186/s12199-021-00953-1
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional survey of depressive symptoms and suicide-related ideation at a Japanese national university during the COVID-19 stay-home order

Abstract: Background We aimed to estimate the prevalence of depressive symptoms as well as suicide-related ideation among Japanese university students during the stay-home order necessitated by the coronavirus disease 2019 pandemic in Japan, and offer evidence in support of future intervention to depression and suicide prevention strategies among college and university students. Methods The data for this cross-sectional study were derived from the Student Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
79
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(94 citation statements)
references
References 33 publications
3
79
0
1
Order By: Relevance
“…As a result, the suicide rates in the affected area did not remarkably increase as compared to those in the non-affected area, because of the support provided for the many evacuees. Under these situations, therefore, ongoing disaster-related mental health interventions based on consensual screening and the high-risk approach (e.g., focused on psychological distress and binge drinking among evacuees) and outreach-based support may have prevented a remarkable increase in suicide rates in the affected area, even during the COVID-19 pandemic: a scenario that generated feelings of loneliness, subsequent depressive states, and binge drinking behavior among the elderly evacuees in the public restoration housing in particular [ 23 , 29 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the suicide rates in the affected area did not remarkably increase as compared to those in the non-affected area, because of the support provided for the many evacuees. Under these situations, therefore, ongoing disaster-related mental health interventions based on consensual screening and the high-risk approach (e.g., focused on psychological distress and binge drinking among evacuees) and outreach-based support may have prevented a remarkable increase in suicide rates in the affected area, even during the COVID-19 pandemic: a scenario that generated feelings of loneliness, subsequent depressive states, and binge drinking behavior among the elderly evacuees in the public restoration housing in particular [ 23 , 29 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in an Irish representative sample, loss of income due to COVID-19 proved to be a risk factor for depression and anxiety [ 14 ]. This is particularly important, since high-intensity stressors, such as low socioeconomic status and symptoms of depression, can be a potential trigger for suicidal ideas and suicide attempts [ 19 ], in addition, depression symptoms seem to affect a larger proportion of young women than men [ 20 ]. In fact, inequalities in income, education and wealth have proved to be an essential determinant of depression [ 21 ] and anxiety [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The correlation was lower in students with higher levels of coping strategies (self-efficacy) than in students with lower levels of coping strategies (self-efficacy). Nomura et al (2021) also reported that interventions should be made because COVID-19 had an effect on the prevalence of depressive symptoms as well as suicide-related ideation among Japanese university students. Szczepańska and Pietrzyka (2021) found a strong correlation ( N = 135) between the severity of lockdown measures during COVID-19 pandemic and the students’ activity levels in public spaces.…”
Section: Introductionmentioning
confidence: 99%